A report in instrumental conducting including an analysis of Dances of Innocence by Jan van der Roost and Air for Band by Frank Erickson - Seago, Erica (Kansas State University, 2016)
Three essential components of wind band conducting are as follows: music selection, score study, and rehearsal planning. This report contains an analysis and rehearsal plan for two band works and a discussion on quality literature selection for band as well as a personal philosophy of music education and student learning. The two works presented are Dances of Innocence by Jan van der Roost and Air for Band by Frank Erickson.
Keywords: Dances of Innocence; Jan van der Roost; Air for Band; Frank Erickson